Risk of spinal cord ischemia after thoracic endovascular aortic repair - Xue, Ling (J Thorac Dis, 2018)
BACKGROUND: Spinal cord ischemia (SCI) is a recognized grave complication after thoracic endovascular aortic repair (TEVAR). The present study aimed to evaluate the incidence and investigate risk of SCI after TEVAR based on current prophylactic strategies designed against established risk factors. METHODS: The study retrospectively reviewed a prospectively maintained database to investigate patients who underwent TEVAR successfully between January 2009 and December 2012 in a single cardiovascular center. Detailed assessment of SCI risk was routinely performed for all patients before TEVAR was carried out. Prophylactic measures, including left subclavian artery (LSA) revascularization, blood pressure augmentation and cerebrospinal fluid (CSF) pressure control after TEVAR, were employed in high-risk patients and physical neurological examinations were regularly done to evaluate SCI after TEVAR. Patients were further divided into SCI group and non-SCI group. RESULTS: A total of 650 patients were enrolled in the study. Eleven patients (1.69%) developed SCI after TEVAR. Baseline level of hemoglobin was significantly lower in the SCI group (113.00 vs. 128.50, P=0.023). More patients in the SCI patients in the SCI group underwent TEVAR under general anesthesia (45.5% vs. 17.7%, P=0.033). A significantly higher incidence of post TEVAR hypotension was found in the SCI group (2.7% vs. 27.3%, P=0.004). Logistic regression analysis revealed that post-TEVAR hypotension (OR, 8.379; 95% CI, 1.833–38.304; P=0.006) was strongly associated with development of SCI and high normal baseline hemoglobin was a protective factor (OR, 0.969; CI, 0.942–0.998; P=0.037). The mortality in hospital and mortality at 1 year were not significant different between the SCI and the non-SCI group (0% vs. 1.6% P=1.000; 9.1% vs. 3.0%, P=0.294, respectively). While length of post-TEVAR stay (13.00 vs. 7.00 days, P=0.000) and length of hospital stay (20.00 vs. 13.00 days, P=0.001) were significantly greater in the SCI group. CONCLUSIONS: Our study revealed that, based on current prophylactic measures to curtail SCI, including LSA revascularization, blood pressure augmentation and CSF pressure control after TEVAR, post-TEVAR hypotension remains a major and independent risk factor for SCI and high normal baseline hemoglobin level is protective. SCI results in longer post-TEVAR stay and hospital stay, but not associated with increased mortality. Robust precautions should be taken against underlying causes for post-TEVAR hypotension and low level of hemoglobin should be avoided.